Čeští krajané v bulharském Ruse (Rusčuku) v prvních dekádách 20. století a jejich spolek „Havlíček“ - Jakoubek, Marek; Mezhlumyan, Marta (Lidé města, 2025)
This text deals with the issue of Czech compatriots in Ruse (Rustchuk) in Bulgaria, and the local compatriots’ association Havlíček. The first part of the article is devoted to the recapitulation of domestic academic interest in Czech and Slovak compatriots in Bulgaria, focusing on the central compatriot organization in the country – the Czechoslovak National House of T. G. Masaryk in Sofia. The second part of the article presents the annotated archival document Colonization and Association Report, written by representatives of the Havlíček Association in 1929 for an exhibition of compatriot associations organized that year in Prague. The document describes the history of the Czech minority in Ruse with special attention placed on the Havlíček Association. As such, it represents a fundamental source for the study of this hitherto rather neglected and lesser known compatriot minority in Bulgaria.